An in vitro experimental study on the relationship between pulsatile tinnitus and the dehiscence/thinness of sigmoid sinus cortical plate. (14th February 2019) - Tian, Shan; Fan, Xingyu; Wang, Yawei; Liu, Zhaohui; Wang, Lizhen
Abstract: Pulsatile tinnitus (PT), characterized as pulse-synchronous, is generally objective. Sigmoid sinus (SS) venous sound is widely suggested to be a possible sound source of PT. The dehiscence and thinness of SS cortical plate (CP) was commonly reported as PT pathology in previous studies, but lack quantitative or biomechanical analysis. In this study, it was aimed to quantify the relationship between venous sound and CP dehiscence/thinness using in vitro experiment. The in vitro models of SS and CP were established based on 3D-printing, with the developed pulsatile venous flow in the SS model. The generated sound signal and the vibration response at the dehiscent/thinned area were analyzed. The sound signal generated in the normal-sized dehiscence model was pulse-synchronous within 100-–400 Hz, which had similar acoustic characteristics as the clinical PT sounds. It was concluded that the pulsatile venous sound is produced at TS-SS junction in case of CP dehiscence. The CP, even a thinned one can effectively diminish the venous sound and sound-generating pulsatile vibration at TS-SS junction. The CP dehiscence would induce pulse-synchronous and high pressure venous sound, as well as pulse-synchronous vibration above 20 Hz, regardless of the dehiscence size. On the contrary, the CP thinness would not induce obvious venous sound or pulsatile vibration above 20 Hz.